Expression of heat-shock protein gp96 in gallbladder cancer and its prognostic clinical significance - Chen, Yongli (Int J Clin Exp Pathol, 2015)
Purpose: To detect the expression and prognostic clinical significance of heat-shock protein gp96 (HSP gp96) in gallbladder cancer. Methods: Immunohistochemistry was used to detect and compare the rate of HSP gp96 expression in 107 samples of gallbladder cancer, 70 of gallbladder adenoma and 67 of chronic cholecystitis. The association of clinicopathological factors and patients’ survival were calculated by univariate and multivariate (Cox proportional hazard regression method) analysis. Results: The expression positive rate of HSP gp96 was 90.7% (97/107) in gallbladder cancer, 71.4% (50/70) in gallbladder adenoma and 47.76% (32/67) in chronic cholecystitis respectively. The positive rate of HSP gp96 in gallbladder cancer tissues was significantly higher than that in gallbladder adenoma and chronic cholecystitis tissues (P < 0.01). Multivariate and Cox regression analysis showed that positive of HSP gp96 (P = 0.026) expression was an independent poor prognostic predictor in gallbladder cancer. Conclusions: HSP gp96-positive expression is closely correlated with poor survival in gallbladder cancer.